Partisipasi Masyarakat Dalam Proses Penyusunan Anggaran Pendapatan Dan Belanja Daerah (APBD) Di Kabupaten Pati - Wardhani, Septian Cahya; , Erma Set iawati, Dr., Akt., M.M (2015)
Regional Budget (APBD) prepared based approach to performance, which is a budgeting system that prioritizes efforts to achieve employment outcomes or outputs of the cost allocation plan or the specified input (Regulation No. 58 of 2005). Public participation in budgeting should be done at each stage of the budget cycle starting from drafting, ratification, implementation, until the responsibility (Mardiasmo, 2002: 70). The purpose of this study was to determine the extent of public participation in budgeting in Pati regency, to determine strategies used so public participation in budgeting is effective in Pati regency, to find out the problems facing the community in preparing the budget participation in Pati regency. This research is a form of qualitative research methods phenomena (phenomenology). Source of data derived from the results of a questionnaire that was filled by NGOs and community Pati regency, and the results of interviews of legislators and the public Pati regency. Data collection techniques in this study were: 1) interviews, and 2) a questionnaire / questionnaire. The results showed that the budget process in Pati regency involves community participation, the strategies used so that public participation in budgeting in the district of starch to be effective it starts from the village, followed Musrenbang formed at the district level, then held Musrenbang at the district level. Results after the effective formulation of Musrenbang finally brought to the legislators, and if not effectively be done plenary session in accordance with the applicable procedures, there are no problems or issues faced by the community in preparing the budget participation in Pati regency, in budgeting is a board member to be transparent and open between the executive and the legislature, and the plenary session was witnessed by many journalists.